What will happen to the jobs? Technology-enabled productivity improvement – good for some, bad for others. (3rd July 2017) - Roos, Göran; Shroff, Zara
ABSTRACT: The article looks at the literature as relates to technology-driven shifts in employment with a specific emphasis on digital technologies. The article looks at both the arguments for a positive outcome and for a negative outcome. The article concludes that there are probably more jobs going to be created than is presented in popular media but that this will be taking place simultaneously with a sharp polarisation of the workforce and an increased uneven global distribution of the jobs created. The key contribution of this paper is that whether the future becomes one of job scarcity and precariasation or one of job abundance and multi-dimensional wealth (economic, environmental, quality of life) cannot be left to the market but is instead a function of the socio-political choices we and our policy-makers make.